Fixed Point of Total Asymptotically Nonexpansive Mappings in Banach Spaces - Kannika Khomphurngson; Nammanee, Kamonrat (Science & Technology Asia, 2024)
In this paper, we present a strong convergence theorem for total asymptotically nonexpansive mappings in a real uniformly convex Banach space.